2017
DOI: 10.1017/jfm.2016.820
|View full text |Cite
|
Sign up to set email alerts
|

Flow structure beneath rotational water waves with stagnation points

Abstract: The purpose of this work is to explore in detail the structure of the interior flow generated by periodic surface waves on a fluid with constant vorticity. The problem is mapped conformally to a strip and solved numerically using spectral methods. Once the solution is known, the streamlines, pressure and particle paths can be found and mapped back to the physical domain. We find that the flow beneath the waves contains zero, one, two or three stagnation points in a frame moving with the wave speed, and describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
90
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 36 publications
9
90
0
Order By: Relevance
“…This critical layer has a Kelvin cat eye structure together with the respective formation of critical points, as numerically illustrated by the authors in Ref. .…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…This critical layer has a Kelvin cat eye structure together with the respective formation of critical points, as numerically illustrated by the authors in Ref. .…”
Section: Introductionmentioning
confidence: 62%
“…The paper by Teles and Peregrine conjectured flow features which were later investigated by both numerical and theoretical researchers. These include numerical studies with traveling waves, such as that by Vasan and Oliveras as well as by Ribeiro et al Applied analysis researchers recently made efforts in understanding the impact of constant vorticity on nonlinear traveling wave solutions. A good source of recent articles is found in the theme volume edited by Constantin .…”
Section: Introductionmentioning
confidence: 99%
“…However, even for constant vorticity, Refs. and others numerically observed overhanging profiles and interior stagnation points.…”
Section: Introductionmentioning
confidence: 75%
“…This contrasts with many other numerical methods, such as those based on surface integro-differential equations (VandenBroeck 1996; Ashton & Fokas 2011) or on the conformal mapping technique (Choi 2009;Ribeiro-Jr et al 2017), which require the results to be mapped back to the physical domain.…”
Section: Computation Of Steady Wavesmentioning
confidence: 99%
“…For a review on the recent rigorous results, the reader can refer to Constantin & Varvaruca (2011) and Kozlov & Kuznetsov (2014). Among the authors using asymptotic methods or purely numerical methods, on can cite Tsao (1959), Dalrymple (1974), Brevik (1979), Simmen & Saffman (1985), Teles da Silva & Peregrine (1988) , Kishida & Sobey (1988), Vanden-Broeck (1996), Swan & James (2001), Ko & Strauss (2008), Pak & Chow (2009), Cheng, Cang & Liao (2009 , Moreira & Chacaltana (2015), Hsu, Francius, Montalvo & Kharif (2016), Ribeiro-Jr, Milewski & Nachbin (2017). Although the recent important theoretical developments have confirmed that periodic waves can exist over flows with arbitrary vorticity, it appears that their stability to infinitesimal disturbances and their subsequent nonlinear evolution have not been studied extensively so far.…”
Section: Introductionmentioning
confidence: 99%